O corpo anoréxico: dos abusos midiáticos às experiências de novos processos comunicativos - Ribeiro, Juliana Costa (2009)
The increasing number of eating disorders in the last decades calls the attention of researchers concerned with body studies in several fields of knowledge. The media and the fashion world emphasize the need of a woman s slim and young body, associated with happiness, wealth, health and success. There is more demand of a slim body among social groups connected with worldwide information. The fear of rejection is usually considered the immediate cause of such radical action. The main objective of this research work is to analyze how the communication processes between the anorectic body and the environment occur, and the possible changes after performing body practices, such as the Vianna s technique. Our hypothesis is that anorectic people live under the mind/body duality paradigm, taking the control of the mind over the body to the last consequences. To understand the symptom of body maps distortion in the brain, we analyzed the works by the neuroscientist Damásio (1995), and the concept of embodied mind concept by Lakoff & Johnson (1999). Then we present historical data on an anorexia outbreak in the Middle Ages, known today as holy anorexia, and the current anorexia nervosa, so as to discuss the mind/body spirit/matter duality in both cases. So we will also discuss the phenomenon of media abuse in advertisements, newspapers, books, TV and Internet, considered to cause the contemporary anorexia nervosa. The theory adopted here is the research works by Katz & Greiner (2005) on the mediabody, which considers the body the primary communication media; by Gail Weiss (1999), on the formulation of body images; by Paul Churchland (2004), who mapped the several types of Cartesian dualisms; and the theoretical work by the Brazilian researchers Letícia Teixeira (2008) and Neide Neves (2008) on Vianna s technique, who helped clarify the idea that an approach based on the body can help an anorectic person to undo the mind/body dichotomy. For the research corpus, we observed two groups of people. The first one is formed by people who had anorexia and recovered from it; the second, by anorectic people under medical treatment who perform Vianna s technique. Field work is being carried out since September 2007. As an outcome, this work proposes changing the discussion focus on anorexia, usually concerned with cultural pressures on psychoanalytical analyses, once it considers this disease as result of a radicalization of the mind/body duality. This separation inquires body s nature as a mediabody and, once abusively highlighted by press, it disguises the disorder as a communicational mass phenomenon, rendering the understanding and treatment in each particular case more complicating